2004
DOI: 10.1161/01.cir.0000148824.93600.f3
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces Neutrophil Accumulation In Vivo Through Generation and Release of CXC Chemokines

Abstract: Background-Angiotensin II (Ang II) is implicated in the development of cardiac ischemic disorders in which prominent neutrophil accumulation occurs. Ang II can be generated intravascularly by the renin-angiotensin system or extravascularly by mast cell chymase. In this study, we characterized the ability of Ang II to induce neutrophil accumulation. Methods and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 24 publications
6
84
0
Order By: Relevance
“…2 for review). Consistent with the latter finding, blockade of AT 1 , the major receptor mediating the inflammatory actions of Ang II, reduces neutrophil recruitment and cytokine release in models of inflammation (12,37,38). However, to our knowledge, the expression of Mas receptor in periarticular tissues was demonstrated for the first time in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2 for review). Consistent with the latter finding, blockade of AT 1 , the major receptor mediating the inflammatory actions of Ang II, reduces neutrophil recruitment and cytokine release in models of inflammation (12,37,38). However, to our knowledge, the expression of Mas receptor in periarticular tissues was demonstrated for the first time in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to inhibiting neutrophil influx due to the inhibition of local production of chemokines, it was possible that Mas agonists could be directly interfering with the process of leukocyte-endothelial cell interaction, hence preventing their influx. In support of the latter possibility, other studies have found that Ang II via AT 1 receptor stimulated leukocyte-endothelium interactions and increased neutrophil migration in vivo (37,38). In our study, treatment with the Mas receptor agonist AVE 0991 significantly inhibited rolling and cell adhesion of leukocytes to endothelial cells in the joint microvasculature of mice subjected to AIA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was mediated by acceleration of macrophage infiltration and necrotic re-absorption. The action of the RAAS in mobilization of inflammatory cells also involves Ang II mediated facilitation of chemokines release, which leads to neutrophil recruitment, as previously described by Nabah et al (37). These effects may contribute to increased neutrophil infiltration into ischemic myocardium, an action that can lead to an abnormal inflammatory response and acute ventricular expansion.…”
Section: The Cardiac Renin-angiotensin-aldosterone Systemmentioning
confidence: 61%
“…55 Classically, chronic RAS activation through AT1R leads to increased blood pressure, renal salt retention, aldosterone release and sympathetic nervous system activation. 56 Locally, stimulation of RASs may influence diverse physiological outputs, especially inflammatory processes through AT1R-mediated stimulation of neutrophil migration 57 and activation of the pro-inflammatory effector NF-κB (nuclear factor-κB) in phagocytes, 58 amongst others. AT1R blockers were effective in counteracting the deleterious inflammatory responses elicited by some bacterial infections, including acute respiratory distress syndrome (ARDS) triggered by Bordetella bronchiseptica 59 and lung colonization by P. aeruginosa.…”
Section: Functional Tests On the Selected Compounds From The Virtual mentioning
confidence: 99%